Management of Adult Patients With Drug Reaction With Eosinophilia and Systemic Symptoms: A Delphi-Based International Consensus - Brüggen, Marie-Charlotte; Walsh, Sarah; Ameri, M Milad; Anasiewicz, Natalie; Maverakis, Emanual; French, Lars E; Ingen-Housz-Oro, Saskia; Abe, Richiiro; Ardern-Jones, Michael; Assier, Haudrey; Barbaud, Annick; Bensaid, Benoit; et al. (JAMA dermatology, 2024)
IMPORTANCE: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare but potentially fatal drug hypersensitivity reaction. To our knowledge, there is no international consensus on its severity assessment and treatment. OBJECTIVE: To reach an international, Delphi-based multinational expert consensus on the diagnostic workup, severity assessment, and treatment of patients with DRESS. DESIGN, SETTING, AND PARTICIPANTS: The Delphi method was used to assess 100 statements related to baseline workup, evaluation of severity, acute phase, and postacute management of DRESS. Fifty-seven international experts in DRESS were invited, and 54 participated in the survey, which took place from July to September 2022. MAIN OUTCOMES/MEASURES: The degree of agreement was calculated with the RAND-UCLA Appropriateness Method. Consensus was defined as a statement with a median appropriateness value of 7 or higher (appropriate) and a disagreement index of lower than 1. RESULTS: In the first Delphi round, consensus was reached on 82 statements. Thirteen statements were revised and assessed in a second round. A consensus was reached for 93 statements overall. The experts agreed on a set of basic diagnostic workup procedures as well as severity- and organ-specific further investigations. They reached a consensus on severity assessment (mild, moderate, and severe) based on the extent of liver, kidney, and blood involvement and the damage of other organs. The panel agreed on the main lines of DRESS management according to these severity grades. General recommendations were generated on the postacute phase follow-up of patients with DRESS and the allergological workup. CONCLUSIONS AND RELEVANCE: This Delphi exercise represents, to our knowledge, the first international expert consensus on diagnostic workup, severity assessment, and management of DRESS. This should support clinicians in the diagnosis and management of DRESS and constitute the basis for development of future guidelines.
Keywords: průzkumy a dotazníky; eozinofilie; delfská metoda; dospělí; Humans; Adult; Drug Hypersensitivity Syndrome; Consensus; lékový hypersenzitivní syndrom; Delphi Technique; Eosinophilia; Surveys and Questionnaires; lidé; konsensus